EQUITY HOLDERS’ MARKET DISCIPLINE IN GCC COUNTRIES - Guermazi, Imene (International Journal of Accounting & Finance Review, 2022)
This paper aims to study Equity holders’(EHs) discipline in three GCC countries, Bahrain, the UAE, and KSA for the period (2004-2014). We test bank risk monitoring in the 2008 crisis period by comparing the perceived risk proxied by BETA during the pre-and post-crisis episodes. We find significant differences in BETA values in Bahrain and the UAE. Then, we use the fixed effect model and the random effect model to regress BETA on CAMEL variables measuring bank risk. We study bank reaction by regression relevant CAMEL variables to EH monitoring on BETA of a lagged period. Our results show that in Bahrain, the coefficients of the variables Liquidity and Size are significant. Thus, EHs, in Bahrain, monitor their bank using financial information on Liquidity and Size. However, we find no responsiveness of the banks to this monitoring. Thus, there is no evidence of EHs’ discipline in GCC countries. We contribute first, to fulfilling the gap in market discipline literature in Emerging countries, specifically, Bahrain, KSA, and the UAE. Second, we shed light on the market discipline of a special type of banking-IBs. Third, we innovate a new monitoring signal, BETA values assessed by EHs. JEL Classification Codes: G21, G12, M41.